Autorzy:Jerzy Janowicz
Wydawnictwo:Nowa Era
Rok wydania:2016
Oblicz 4.67 gwiazdek na podstawie 6 opinii

`a)\ (5^-5*125^3*25^-4)/625^-2=(5^-5*(5^3)^3*(5^2)^-4)/(5^4)^-2=(5^-5*5^(3*3)*5^(2*(-4)))/(5^(4*(-2)))=` 

`\ \ \ =(5^-5*5^9*5^-8)/(5^-8)=5^-5*5^9=5^(-5+9)=5^4=625`  

 

 

`b)\ ([(1/3)^-2]^3+[(2/3)^3]^-1)/((3^-2)^6:(3^5)^-3)=((1/3)^(-2*3)+(2/3)^(3*(-1)))/(3^(-2*6):3^(5*(-3)))=((1/3)^-6+(2/3)^-3)/(3^-12:3^(-15))=`  

`\ \ \ =(3^6+(3/2)^3)/(3^(-12-(-15)))=(3^6+(3^3)/2^3)/(3^(-12+15))=(3^6+3^3/2^3)/3^3=3^6/3^3+(3^3/2^3)/3^3=3^(6-3)+3^3/2^3*1/3^3=3^3+2^3=27+8=35`